SWOT analysis to assess implementation of medicinal plants and its development based on the perceptions of teachers and stakeholders - Lestari, Endang Sri (Priviet Social Sciences Journal, 2026)
Education about medicinal plants facilitates the development of scientific research skills, including field data collection, laboratory analysis, and the writing of research reports in line with the developments in 21st-century education, which emphasize knowledge-based skills. This research aims to evaluate the implementation of biology education with the integration of medicinal plant materials in an effort to harness local potential, viewed from the perspectives of educators and policy stakeholders using SWOT analysis. This study employs a qualitative research approach with a case study design, allowing for an in-depth understanding of the implementation of biology education and the prospects for the development of medicinal plant materials in several schools. Qualitative research methods provide a profound insight into the implementation of biology education, the prospects for the development of medicinal plant materials, and the identification of factors influencing its implementation. The research was conducted in senior high schools (SMA) in Karanganyar. School selection was done purposively, considering variables such as the level of implementation success, geographical location, and student population diversity. Research participants include Biology teachers, students, and education policy stakeholders. The research results provide valuable insights into how education about medicinal plants can influence students' understanding of biodiversity, ecosystem roles, as well as environmental and cultural impacts. Furthermore, this research has identified challenges and opportunities in integrating medicinal plant materials into biology learning.